IDENTIFIKASI KETERAMPILAN PROSES SAINS SISWA SMK PADA POKOK BAHASAN RANGKAIAN ARUS SEDERHANA - Hediana Alfian; Supeno Supeno; Sri Handono Budi Prasutowo (JURNAL PEMBELAJARAN FISIKA, 2018)
Science process skills is a capability which purpose is to develop and apply students' knowledge in solving problems so that students are trained and able to understand a concept scientifically. This article aims was to identify students science process skills conducted through tests on the subject of simple current circuits. This study was conducted with 18 students as respondents. The instrument used is 2 problems with each question consisting of 4 points. The results showed that with a percentage of 54.24%. Of the 6 indicators contained in the skills of the science process, the average percentage of the highest indicator is on the plan indicator to test the hypothesis with a percentage of 72.56% and the lowest indicator is the result of experiments with a percentage of 39.77%. The results indicate that students are not accustomed to experimenting in the learning process at school.Kata kunci : Identifikasi, Keterampilan proses sains, Rangkaian arus sederhana